En passant par : une expression en voie de grammaticalisation ? - Dejan Stosic (Corela)
In this paper, we analyse the morpho-syntactic and semantic functioning of the expression en passant par in French, in synchrony as well as in diachrony (1500-2011). A corpus-based study brings clearly out two very different behaviours of this expression respectively in the sixteenth century and in Modern French. All differences revealed by our analysis suggest an obvious evolution that results in a coexistence in contemporary French of a free construction corresponding to the gerund of the verb passer ‘to pass’ followed by a PP in par (e.g. J’ai vu une boulangerie en passant par cette rue) with the non compositional expression en passant par, similar in many ways to prepositions (e.g. Il a tout lu de Montaigne à Gary en passant par Gautier et Balzac). Neither lexicographers nor linguists acknowledge this prepositional status of en passant par. In order to explain this double behaviour of en passant par in Modern French, we study the hypothesis of an ongoing grammaticalization, and test it on the basis of data drawn from written literary and journalistic texts. More generally, this study brings to the fore the semantic and functional consequences of the categorial change that currently affects the gerund of the motion verb passer in French when followed by par.